Bacteriophilic tetra-p-guanidinoethyl-calix[4]arene derived polymers. Syntheses and E. coli sequestration studies. (14th July 2016) - Lemée, Frédéric; Mourer, Maxime; Aranda, Lionel; Clarot, Igor; Regnouf-de-Vains, Jean-Bernard
Abstract : New resins functionalized by the antibacterial tetra- p -guanidinoethylcalix[4]arene were synthesized, and their bacteriophilic properties were evaluated ( E. coli ) by capillary electrophoresis. Abstract : The antibacterial tetracationic tetra- p -guanidinoethylcalix[4]arene developed by our team has been anchored through bottom-up or top-down pathways to the surface of Merrifield and Wang benzaldehyde resins; the attachment involved either a pyridinium linker or an imine/amine one. The grafting yields were evaluated by elemental analysis through the nitrogen content. Their sequestering properties towards bacteria were evaluated, using E. coli as a model, by capillary electrophoresis (CE) which showed their efficiencies and their bacteriophilic behaviors. All the new materials were compared to two pyridinium-derived Merrifield resins in terms of effective capture, efficiency, and removal coefficients, showing that some of these calixarene-derived resins are good bacteriophilic materials. Confirmation of such behavior has been provided by microscopy.